Reactivation of chlamydial genital tract infection in mice. - Cotter, T W (1997)
A model was developed to study chlamydial quiescence in C3H/HeN (C3H) and C57BL/6N (C57) mice following genital tract infection by Chlamydia trachomatis MoPn. Reactivation of chlamydial shedding following immunosuppression indicated that viable MoPn remained in the genital tract for up to 4 or 5 weeks after the apparent clearance of a primary infection. Either cyclophosphamide or cortisone acetate treatment could cause reactivation, but cyclophosphamide was more effective. However, the frequency of reactivation by either drug diminished with time in both mouse strains. Progesterone treatment prior to infection of C57 mice greatly reduced the frequency of reactivation by cyclophosphamide and also correlated with the development of marked fluid accumulation and distension of the uterine horns in the vast majority of those animals. This pathology was apparent by 5 to 7 weeks postinfection and was consistently seen through 110 days postinfection. Neither of these phenomena was observed in C57 mice that had not been treated with progesterone or in C3H mice under any conditions tested. The infecting dose of MoPn did not clearly influence the frequency of reactivation in either inbred strain as defined by this model.